COMPARATIVE RESEARCH ON TAX APPLICATION TO ROYALTIES CONTRACTS - Pumpure, Inga; Mietule, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Royalties and copyright as an economic category and topical legal terms scored in the 20th century, while improving the country's fiscal policy and differentiating tax items; the usage of economic categories of "royalties" expands and becomes important. To be able to compare how royalties beneficiaries comply with legislative acts and requirements relating to the taxation of another European Union Member State, the author compares the taxation in Latvia and Estonia. In 2018, an ambitious tax reform has been implemented in both countries.The aim of the research: to conduct a comparative study on tax requirements and issues related to royalties in Latvia and Estonia. To achieve the aim of the research, the monographic method, the methods of comparative and analytical analysis, and the grouping and graphic methods were used additionally. In the result of the research study, the author concluded that, despite the unification of tax systems in the Baltic States, the regulatory framework is different in both countries. Estonian taxpayers' tax burden in respect of royalties is significantly higher than that of the Latvian income recipient